Exlibris Bibliographicis Hermann Wiese Johannes Trithemius [A. Piller]. - Piller, Attila (1961- ). (1985)
Podobizna Johannes Trithemius w stroju biskupim. U góry w gotyckich łukach napis: Exlibris Bibliographicis Hermann Wiese.